2021
DOI: 10.1126/sciadv.abg6497
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-11 signaling promotes cellular reprogramming and limits fibrotic scarring during tissue regeneration

Abstract: Damage-induced fibrotic scarring limits tissue regeneration in mammals and is a leading cause of morbidity. In contrast, species like zebrafish can regenerate damaged tissues without excessive fibrosis. However, whether specific signaling pathways can both limit fibrosis and promote regeneration is unclear. Here, we show that interleukin-11 (Il-11)/Stat3 signaling has such a dual function. Zebrafish lacking Il-11 receptor function display severely compromised heart, fin, and scale regeneration. Deep phenotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 86 publications
(138 reference statements)
4
76
0
Order By: Relevance
“…1a), which we read out later in the adult heart (all lineage trees are shown in Supplementary Figs. [14][15][16][17]. By sequencing scars and transcriptomes from the same single cells, we could build lineage trees that revealed the shared developmental origins of the cell types (Fig.…”
Section: Identification Of Proregenerative Cardiac Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a), which we read out later in the adult heart (all lineage trees are shown in Supplementary Figs. [14][15][16][17]. By sequencing scars and transcriptomes from the same single cells, we could build lineage trees that revealed the shared developmental origins of the cell types (Fig.…”
Section: Identification Of Proregenerative Cardiac Fibroblastsmentioning
confidence: 99%
“…Many pathways and factors involved in heart regeneration have been described [7][8][9][10][11] . Important molecular signals for zebrafish heart regeneration emanate from the epicardium and endocardium 3,[11][12][13][14] . Other cell types are required for regeneration: inflammation is an early response to cryoinjury, and depletion of macrophages leads to delayed regeneration 15,16 .…”
mentioning
confidence: 99%
“…In the present experiments, we found that tissue content of IL-6/STAT3 signaling was an exquisite inducer of cardiomyocyte into a dedifferential status, likely acting in a same way as another IL-6 family members, OSM and IL-11 in mammalian heart [ 11 ] and zebrafish [ 10 ], suggesting that IL-6 family/STAT3 signaling is a conservative pathway to initiate dedifferential step under malignant stress [ 49 ]. The dedifferentiated cardiomyocytes exhibited a typical morphological alternation characterized by sarcomeric disorganization, relocation cardiac proteins towards the cell wall (marginalization), reduced cell–cell junctions and virtually increased cell mitosis markers (Aurora B and pH3 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of cardiac dedifferential process involves multiple regulatory molecules, including microRNA, transcriptional factors, and paracrine cytokines [ 9 ]. Interleukin-6 (IL-6) family members are known to be important regulators that orchestrate dedifferential process during heart regeneration [ 10 ]. Oncostatin M (OSM) has been reported to be a master regulator of cardiomyocyte dedifferentiation in adult mammalian heart [ 11 ], and recently also to play a role in neonatal heart regeneration [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation